Synthesis and characterization of NiO–Bi2O3 nanocomposite material for effective photodegradation of the dyes and agricultural soil pollutants. (15th June 2023) - Masula, Keshavulu; Sreedhar, P.; Vijay Kumar, P.; Bhongiri, Yadagiri; Pola, Someshwar; Basude, Manohar
Abstract: Synthesis and characterization of the pristine NiO, Bi2 O3 and composite NiO–Bi2 O3 (NBO) nano material systems with the modified surface morphology is reported. The NBO and pure oxide materials are thoroughly characterized with various spectroscopic methods such as XPS, p-XRD, FTIR, Raman, UV–vis-DRS, PL, FESEM and HRTEM analysis. XRD results showed the formation of a new γ-phase of Bi2 O3 after incorporating Ni on its surface. XPS and EDX analysis confirmed the presence of both Ni 2+ and Bi 3+ in the nanoparticles. HRTEM analysis showed NiO nanospheres on Bi2 O3 nanorods with 13–18 nm nanoparticle sizes Furthermore, as a result of composite phase formation, a substantial decrease in bandgap from 3.28 to 2.62 eV is found, which was captivating to study the visible light energy induced photodegradation of methylene blue (MB), methyl orange (MO) dyes and agricultural soil pollutants (ASP). The effect of pH, dosage, and scavenger's studies are investigated to establish the mechanism of the active species of the photodegradation process and which is supported by photocurrent and EIS studies. Under the optimal framework, the photocatalytic degradation efficacy of the MB, MO dyes and ASP degradation with NBO was 95, 90 and 94% respectively. Additionally, HPLC analysis of initial and final samples of dyes was studied and TOC analysis for ASP examined. NBO catalyst was recovered and reused umpteen times with marginal change in photocatalytic efficiency. Graphical abstract: NBO nano composite material act as photocatalyst for photodegradation of MB and MO dyes and agricultural soil pollutants under visible light treatment because of electron-hole pair recombination is low. Image 1 Highlights: Preparation of pure NiO, Bi2 O3 and new NiO–Bi2 O3 composite nanomaterials by wet-impregnation method and thoroughly characterized. Photodegradation of organic dye pollutants such as methylene blue, methyl orange under visible light irradiation. Photodegradation of agricultural soil pollutants was investigated and identified with LC-MS data. Mechanistic studies established that the active species are hydroxy radials via several foragers studies.